Innovative activity of a court - V. V. Lazarev (Russian Journal of Economics and Law, 2021)
Objective: to study the innovative activity of the judicial authorities of the Russian Federation.Methods: dialectical approach to the cognition of social phenomena, which determined the choice of the following research methods: formal-logical, comparative-legal, and sociological.Results: the article attempts to comprehend the court activity as creative activity introducing many novelties to the interpretation of factual circumstances, to the understanding of legal values, and to the implementation of the latter. A court decision is always innovative to the extent that it introduces a novelty into the law and fact interpretation, to the extent that it gives an answer to a question that allowed for different decisions, and to the extent that it removes the existing uncertainty. The level of innovativeness depends on the state of actual circumstances, the level of established judicial practice, the novelty and degree of certainty of legal norms, the sufficiency of legislative regulation, as well as on the competence of a particular court. Courts are often producers of scientific ideas, political and legal concepts, legal and moral principles of law. In this case, the mutual connection between legal science and practice is emphasized. On the one hand, it is judicial practice that feeds the development of the legal sciences, and on the other hand, this practice itself is constantly fertilized by the intelligence of scientific research addressed to it.Scientific novelty: innovations in court decisions are permissible if they meet the general requirements of constitutionalism, are made within the framework of the substantive law and do not go beyond the authorities of the relevant body. Various court decisions are innovative to varying degrees, but they do not lose their other positive qualities if innovation is viewed only in a subjective light in relation to the given circumstances and given participants in public relations. Recognition of the innovative nature of judicial activity at the theoretical level requires the full-fledged legal recognition of judicial precedent as a source of Russian law.Practical significance: the conclusions and provisions of the article can be used in scientific, legislative and law enforcement activities, the educational process of educational organizations of higher education.